Transplantation technologies for treatment of carbohydrate metabolism disorders - V. Е. Zagainov; A. V. Meleshina; К. G. Korneva; S. А. Vasenin; E. V. Zagaynova (Вестник трансплантологии и искусственных органов, 2020)
The review includes results of retrospective and prospective clinical studies (foreign and national) and guidelines on the use of transplantation technologies for treatment of type 1 diabetes and pancreatogenic diabetes in chronic pancreatitis and pancreatic conditions. Modern data on prevalence of diabetes and modern insulin delivery methods are presented. Results of transplantation of pancreas and islets of Langerhans in primary insulin-dependent conditions are considered. Analysis of the technology for isolation and autotransplantation of islets after pancreatectomy in chronic pancreatitis and benign tumor diseases are given.